PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITAS LAPORAN KEUANGAN DAERAH TERHADAP PENGGUNAAN INFORMASI KEUANGAN DAERAH (Studi Kasus pada Pemerintahan Kota Pekanbaru) - Fera Maydia Sari; Taufeni Taufik; Devi Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to examinate and explain the effect of presentation of local financial report and accessibility of local financial report againts the use of local financial information. The population in this research is external user of financial report in government Pekanbaru which includes member of DPRD, Inspektorat personel and BPK personel. The data were analyzed to test the hypothesis using multiple regression analysis approach. The result of this research show that presentation of local financial report and accessibility of local financial report affect the use of financial report.Keywords: Presentation Of Local Financial Report, Accessibility Financial Report, and The Use Of Financial Report.